A carbon-wrapped alloy catalyst and its preparation method and application

By performing heat treatment in reducing gas and annealing treatment with carbonized compounds, carbonized alloy catalysts are formed, and the problem of insufficient stability of high-supported alloy catalysts is solved, and a catalyst with high stability and activity is achieved.

CN117239150BActive Publication Date: 2025-03-14SINOHYKEY TECHNOLOGY (GUANGZHOU) CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311328041.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-13
Publication Date
2025-03-14
Estimated Expiration
2043-10-13

AI Technical Summary

Technical Problem

The existing high-supported alloy catalysts have problems such as support defects and high oxygen content, and the annealing temperature of the existing carbon-encapsulated platinum alloy catalysts is too high, which damages the alloy structure and leads to a decrease in activity.

Method used

Reducing gas is used for heat treatment to improve catalyst support defects and oxygen content, and increase the degree of graphitization of the support to alleviate carbon corrosion. Then, the carbon-encapsulated platinum alloy catalyst is formed by the combined action of the carbonized compound, the ligand compound and the carbonization catalyst to improve its stability.

Benefits of technology

It is achieved without destroying the platinum alloy structure, improves the oxygen reduction electrocatalytic stability of the catalyst, improves the support defects and oxygen content, and extends the life of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117239150B_ABST
    Figure CN117239150B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of fuel cell technology, and specifically relates to a carbon-wrapped alloy catalyst, a preparation method and application thereof. The preparation method of the carbon-wrapped alloy catalyst comprises the following steps: S1, heat-treating the catalyst under a reducing gas atmosphere, mixing the heat-treated catalyst with a carbonized compound, a ligand compound, a carbonized catalyst, and a solvent, ultrasonically dispersing, stirring, centrifuging, and drying to obtain a powder; S2, annealing the obtained powder under a reducing gas atmosphere, dispersing the annealed powder in an acid solution, heating, filtering, and vacuum drying to obtain the carbon-wrapped alloy catalyst; the catalyst is a platinum alloy catalyst or an alloy catalyst made from a carrier and a metal precursor. The carbon-wrapped alloy catalyst prepared by the present invention has high stability, and can overcome the carrier defects and the problem of insufficient stability caused by high oxygen content in existing high-load alloy catalysts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of fuel cells, and in particular relates to a carbon-wrapped alloy catalyst and a preparation method and application thereof. Background Art

[0002] The excessive use of fossil fuels has brought severe challenges to energy and the environment. The development of clean energy conversion technology is expected to solve such problems. Proton exchange membrane fuel cells (PEMFCs) convert chemical energy directly into electrical energy by electrochemically oxidizing renewable fuels (such as hydrogen) at the anode and reducing oxygen to water at the cathode. Proton exchange membrane fuel cell technology is currently being widely studied and developed due to its high energy conversion efficiency, almost no pollution, and potential large-scale application. Platinum is often used to catalyze the oxygen reduction reaction (ORR) in commercial PEMFCs, but due to the slow kinetics of the oxygen reduction reaction (ORR), the catalytic activity of platinum for ORR is still several orders of magnitude lower than that of the anode HOR (hydrogen oxidation reaction) (S Guo, S Zhang, S Sun, Angew. Chem. Int. Ed. 2013, 52, 8526.). Therefore, the large-scale promotion and application of fuel cells requires the development of low-cost, highly active, and durable ORR catalysts, thereby further reducing the catalyst cost.

[0003] Among the various innovative methods for many new ORR catalysts, alloying Pt with transition metals (Fe, Co, Ni, etc.) is widely considered to be a promising method to improve the performance of the catalyst, reduce the amount of platinum, and thus reduce the cost of the catalyst. YYoo, JM Yoo, et al. adjusted the d-band center of Pt by introducing transition metals to enhance the performance of the oxygen reduction reaction, thereby achieving the expected catalytic effect of ORR in fuel cells (Y Yoo, JM Yoo, et al, J.Am.Chem.Soc.2020,142,14190.). However, compared with Pt-based catalysts, alloy catalysts are not stable enough, and the stability of alloy catalysts needs to be further improved to meet the needs of large-scale commercial applications in hydrogen fuel cells.

[0004] The main reasons for the insufficient stability of alloy catalysts are: (1) The most commonly used carbon carrier is Vulcan XC-72 produced by Cabot Corporation. This carbon carrier has many defects and a high oxygen content, which is beneficial to increasing the platinum loading, but at the same time it will aggravate carbon corrosion. The corrosion of the carbon carrier will aggravate the agglomeration and loss of the alloy. In addition, the presence of Pt will accelerate the corrosion of the carbon carrier, resulting in a further decrease in the life of the hydrogen fuel cell (Roen LM, Paik CH, Jarvi D. Electrochem Solid State Lett, 2004, 7(1): A19). Luo Xuan et al. calcined the carbon support at different temperatures and found that the stability of the support and the corresponding Pt-based catalyst after calcination was improved. In particular, the ECSA of the catalyst treated at 2100°C was still 82.4% after oxidation at 1.75V for 10 minutes; while the ECSA of the unmodified catalyst was almost completely lost after oxidation at 1.75V for 10 minutes (Luo Xuan, Hou Zhongjun, Ming Pingwen et al. Journal of Catalysis, 2008(04):330-334.). In addition, Chen M et al. deposited metal precursors on nitrogen / metal co-doped large-size graphene tubes (NGTs) and formed PtM (M: Co and Ni) alloys during annealing, which greatly improved the stability of the catalyst. The PtM (M: Co and Ni) alloy supported on highly graphitized graphene tubes can retain 70% of its electrochemical surface area (ECSA) after 20,000 potential cycles (0.6-1.0 V vs. RHE) (Chen M, Sooyeon H, Li J, et al. Nanoscale, 2018: 10.1039. C8NR05888A-.). Although increasing the degree of graphitization can alleviate carbon corrosion, it also makes the surface of the carbon support chemically inert, making it difficult to evenly disperse the alloy catalyst on the carbon support (Rong Junfeng, Zhao Hong, Wang Houpeng, et al. Beijing: CN114430049A, 2022-05-03.); (2) During the membrane electrode test, transition metals are easily precipitated from the alloy, causing the membrane electrode durability to drop sharply (Wu Shouliang, Liu Jun, Zhang Xian, Wang Xinlei. Anhui Province: CN112615016A, 2021-04-06.). Recently, Li et al. formed a "catalyst armor" by carbonizing oleylamine ligands to protect the internal Pt nanoparticles from damage and enhance the stability of the catalyst (Li Z, Yang D, Dong A, et al. Advanced Materials, 2022, 34: 2202743). However, their research is all about treating Pt / C catalysts with low platinum loading, and too high annealing temperature can easily destroy the platinum alloy structure and cause its activity to decrease. In addition, there is little research on improving the stability of platinum alloy catalysts with high platinum loading. Therefore, there is a need for a method to improve catalyst defects and oxygen content, and to alleviate alloy dissolution to improve its stability. Summary of the invention

[0005] The present invention aims to provide a carbon-wrapped alloy catalyst and a preparation method and application thereof. The carbon-wrapped alloy catalyst prepared by the present invention has high stability and can overcome the problems of carrier defects and insufficient stability due to high oxygen content in existing high-load alloy catalysts (platinum content ≥ 20%), as well as the problem that the annealing temperature of the current carbon-wrapped alloy catalyst is too high, thereby destroying the alloy structure and causing its activity to decrease.

[0006] In order to achieve the above object, the present invention adopts the following technical scheme: a method for preparing a carbon-wrapped alloy catalyst, comprising the following steps:

[0007] S1. heat-treating the catalyst under a reducing gas atmosphere, mixing the heat-treated catalyst with a carbonized compound, a ligand compound, a carbonized catalyst, and a solvent, ultrasonically dispersing, stirring (so that the carbonized compound, the ligand compound, and the carbonized catalyst are uniformly adsorbed on the catalyst surface through coordination), centrifuging, and drying to obtain a powder;

[0008] S2, annealing the obtained powder in a reducing gas atmosphere, dispersing the annealed powder in an acid solution, heating, filtering, and vacuum drying to obtain the carbon-encapsulated alloy catalyst;

[0009] The catalyst is a platinum alloy catalyst or an alloy catalyst made from a carrier and a metal precursor.

[0010] Preferably, the reducing gas in steps S1 and S2 includes at least one of 5% hydrogen-argon mixed gas, 5% carbon monoxide-helium mixed gas, and 5% ammonia-nitrogen mixed gas, wherein the 5% content ratio is the volume percentage of the reducing gas in the system.

[0011] Preferably, the platinum alloy catalyst includes at least one of PtCo / C, PtCoNi / C and PtNi / C.

[0012] Preferably, the platinum content in the platinum alloy catalyst is ≥ 20%.

[0013] Preferably, the carrier includes at least one of acetylene black, carbon black, carbon nanotubes, mesoporous carbon, graphene, carbon nanowires, and graphite fibers.

[0014] Preferably, the metal precursor includes at least one of chloroplatinic acid, platinum chloride, platinum acetylacetonate, cobalt acetylacetonate, cobalt chloride, nickel acetylacetonate, iron nitrate, and copper acetylacetonate.

[0015] The preparation method of the alloy catalyst of the present invention comprises the following steps: dispersing the carrier in ethylene glycol, ultrasonically dispersing for 30-60 minutes, adding a metal precursor, continuously stirring for 12-24 hours, raising the reaction temperature to 180°C-200°C, refluxing for 8-10 hours, cooling, centrifuging, and vacuum drying to obtain the alloy catalyst.

[0016] The carbonized compound of the present invention is a compound that can form a carbon layer on the catalyst surface through a certain process and heat treatment process.

[0017] Preferably, the carbonized compound includes at least one of malic acid, dopamine, polydopamine, oleylamine, glucose and sucrose.

[0018] The ligand compound of the present invention is a compound that can decompose and generate gas during the process of treating the catalyst together with the carbonized compound, thereby generating a microporous structure in the carbon layer.

[0019] Preferably, the ligand compound includes at least one of formic acid, thiourea, ammonia monohydrate, ammonium carbonate and urea.

[0020] The carbonization catalyst of the present invention is a metal catalyst that can catalyze the carbonization of carbonized compounds to form a carbon layer at a relatively low heat treatment temperature.

[0021] Preferably, the carbonization catalyst includes at least one of cobalt chloride, cobalt nitrate, nickel chloride and nickel nitrate.

[0022] Preferably, the solvent is alcohol or an alcohol aqueous solution. The amount of the solvent added is 8-15 mL.

[0023] Preferably, the mass ratio of the heat-treated platinum alloy catalyst to the carbide compound, the ligand compound, and the carbide catalyst is 1: (1-10): (0.2-2): (0.1-1). It can be understood that the mass ratio of the platinum alloy catalyst to the carbide compound, the ligand compound, and the carbide catalyst includes but is not limited to 1: 1: 0.2: 0.1, 1: 10: 2: 1, 1: 3: 1: 0.4, 1: 2: 0.5: 0.5, 1: 8: 1: 0.1, 1: 5: 1.5: 1, 1: 5: 1: 1.

[0024] Preferably, the mass ratio of the metal precursor to the carrier, the carbide compound, the ligand compound, and the carbide catalyst is 1: (0.5-1): (0.8-8): (0.17-17): (0.09-0.9). It can be understood that the mass ratio of the metal precursor to the carrier, the carbide compound, the ligand compound, and the carbide catalyst includes but is not limited to 1: 0.5: 0.8: 0.17: 0.09, 1: 1: 8: 17: 0.9, 1: 0.6: 4: 1: 0.5, 1: 0.8: 5: 10: 0.3, 1: 0.5: 8: 15: 0.9, 1: 1: 1: 1: 0.9.

[0025] Preferably, the heat treatment temperature is 200-400° C., and the heat treatment time is 1-2 hours.

[0026] Preferably, the ultrasonic dispersion time is 10-30 minutes.

[0027] Preferably, the stirring time is 12-24 hours.

[0028] Preferably, the annealing treatment is performed at a temperature of 400-500° C. and for a time of 2-4 hours.

[0029] Preferably, the concentration of the acid solution is 1 M-1.5 M. The acid solution can be selected from strong acid solutions such as HCl, sulfuric acid, and nitric acid in the art.

[0030] Preferably, the heating is to raise the temperature to 70-80° C., and the heating time is 2-12 hours.

[0031] Preferably, the vacuum drying is maintained at 60° C. for 4-6 hours.

[0032] The present invention first utilizes reducing gas to heat treat the alloy catalyst at a certain temperature, improves the defects and oxygen content of the catalyst carrier, and increases the degree of graphitization of the carrier to alleviate carbon corrosion. Subsequently, the platinum alloy catalyst is post-treated by annealing at a certain temperature using a carbonized compound, a ligand compound and a carbonized catalyst to alleviate alloy dissolution and improve its stability. The present invention improves the corrosion resistance of the carrier by treating a catalyst with a high platinum content with a reducing gas, thereby reducing the agglomeration and loss of the alloy catalyst; at the same time, the carbonized catalyst is used to reduce the processing temperature for forming the carbon-encapsulated alloy catalyst, effectively avoiding the defect of the carbon-encapsulated platinum alloy catalyst in the prior art that the annealing temperature is too high, which destroys the platinum alloy structure and causes its electrocatalytic activity to decrease, thereby effectively improving the oxygen reduction electrocatalytic stability of the platinum alloy catalyst without destroying the platinum alloy structure and reducing its oxygen reduction electrocatalytic activity.

[0033] The present invention also claims protection for a carbon-wrapped alloy catalyst prepared by the preparation method of the carbon-wrapped alloy catalyst.

[0034] The present invention also claims to protect the use of the carbon-wrapped alloy catalyst in preparing a fuel cell.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] The carbon-wrapped alloy catalyst prepared by the invention has the advantages of high stability, high catalytic activity, etc., can improve the defects and oxygen content of the catalyst carrier, and increase the graphitization degree of the carrier to alleviate carbon corrosion. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a transmission electron microscopy image of the PtCo / C catalyst selected in the present invention (Pt content is 28%).

[0038] Figure 2 This is a transmission electron micrograph of the carbon-wrapped PtCo / C catalyst prepared in Example 1 of the present invention.

[0039] Figure 3 This is a transmission electron microscopy image of the carbon-wrapped PtCo / C catalyst prepared in Comparative Example 1 of the present invention.

[0040] Figure 4 This is a transmission electron microscopy image of the carbon-wrapped PtCo / C catalyst prepared in Comparative Example 2 of the present invention.

[0041] Figure 5 The cyclic voltammograms of the carbon-wrapped PtCo / C catalysts prepared in Example 1 of the present invention and Comparative Examples 1-2 are shown.

[0042] Figure 6 The linear voltammograms of the carbon-wrapped PtCo / C catalysts prepared in Example 1 of the present invention and Comparative Examples 1-2 are shown.

[0043] Figure 7 The cyclic voltammograms of the carbon-wrapped PtCo / C catalysts prepared in Examples 2-4 of the present invention and Comparative Examples 11-12 are shown.

[0044] Figure 8 Linear voltammograms of carbon-wrapped PtCo / C catalysts prepared in Examples 2-4 of the present invention and Comparative Examples 11-12.

[0045] Fig. 9 The cyclic voltammograms of the carbon-wrapped PtCo / C catalysts prepared in Comparative Examples 6-10 of the present invention are shown.

[0046] Fig.10 The linear voltammograms of the carbon-wrapped PtCo / C catalysts prepared in Comparative Examples 6-10 of the present invention.

[0047] Fig.11 The cyclic voltammograms of the carbon-wrapped PtCo / C catalysts prepared in Example 5 of the present invention and Comparative Examples 3 to 5 are shown.

[0048] Fig.12 The linear voltammograms of the carbon-wrapped PtCo / C catalysts prepared in Example 5 of the present invention and Comparative Examples 3 to 5 are shown.

[0049] Fig.13 This is the polarization current curve of the commercial PtCo / C catalyst after accelerated durability testing.

[0050] Fig.14 This is a polarization current curve of the carbon-wrapped PtCo / C catalyst prepared in Example 1 of the present invention after accelerated durability testing. DETAILED DESCRIPTION

[0051] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0052] In the embodiments and comparative examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.

[0053] Example 1

[0054] S1. Put a PtCo / C catalyst (Pt content is 28%) in a crucible, and then place it in a 5% hydrogen-argon mixed gas atmosphere at 400°C for 2 hours to obtain a heat-treated PtCo / C catalyst; take 50 mg of the heat-treated PtCo / C catalyst in a flask, then add 50 mg of urea, 200 uL of oleylamine, 20 mg of cobalt nitrate and 10 ml of isopropanol / water (volume ratio 50:50) and ultrasonicate for 10 minutes, then place the mixture in a 25°C water bath and stir for 16 hours, collect the product by centrifugation (10000 r.pm, five minutes), and vacuum dry the product at 60°C for 6 hours to obtain a powder;

[0055] S2. The obtained powder is maintained at 400° C. for 2 hours in a 5% hydrogen-argon mixed gas atmosphere, and finally dispersed in 1M HCl, heated to 70° C. and maintained for 2 hours, filtered, and vacuum dried at 60° C. for 6 hours to obtain the carbon-encapsulated PtCo / C catalyst.

[0056] The ligand compound selected in this embodiment can be replaced by any one of formic acid, thiourea, ammonia monohydrate, and ammonium carbonate; the carbonization compound selected can be replaced by any one of malic acid, dopamine, polydopamine, glucose, and sucrose; the carbonization catalyst selected can be replaced by any one of cobalt chloride, nickel chloride, and nickel nitrate.

[0057] Example 2

[0058] S1. Put a PtCo / C catalyst (Pt content is 28%) in a crucible, and then place it in a 5% hydrogen-argon mixed gas atmosphere at 400°C for 2 hours to obtain a heat-treated PtCo / C catalyst; take 50 mg of the heat-treated PtCo / C catalyst in a flask, then add 50 mg of thiourea, 100 mg of oleylamine, 20 mg of cobalt nitrate and 10 ml of isopropanol / water (volume ratio 50:50) and ultrasonicate for 10 minutes, then place the mixture in a 25°C water bath and stir for 16 hours, collect the product by centrifugation (10000 rpm, five minutes), and vacuum dry the product at 60°C for 6 hours to obtain a powder;

[0059] S2. The obtained powder is maintained at 400° C. for 2 hours in a 5% hydrogen-argon mixed gas atmosphere, and finally dispersed in 1M HCl, heated to 70° C. and maintained for 2 hours, filtered, and vacuum dried at 60° C. for 6 hours to obtain the carbon-encapsulated PtCo / C catalyst.

[0060] The ligand compound selected in this embodiment can be replaced by any one of urea, formic acid, ammonia monohydrate, and ammonium carbonate; the carbonization compound selected can be replaced by any one of malic acid, dopamine, polydopamine, glucose, and sucrose; the carbonization catalyst selected can be replaced by any one of cobalt chloride, nickel chloride, and nickel nitrate.

[0061] Example 3

[0062] S1. PtCo / C catalyst (Pt content is 28%) is placed in a crucible, and then placed in a 5% hydrogen-argon mixed gas atmosphere at 400°C for 2 hours to obtain a heat-treated PtCo / C catalyst; 50 mg of the heat-treated PtCo / C catalyst is placed in a flask, and then 100 mg of urea, 615 uL of oleylamine, 100 mg of cobalt nitrate and 10 ml of isopropanol / water (volume ratio 50:50) are added and ultrasonicated for 10 minutes, and then the mixture is placed in a 25°C water bath and stirred for 16 hours, the product is collected by centrifugation (10000 r.pm, five minutes), and the product is vacuum dried at 60°C for 6 hours to obtain a powder;

[0063] S2. The obtained powder is maintained at 400° C. for 2 hours in a 5% hydrogen-argon mixed gas atmosphere, and finally dispersed in 1M HCl, heated to 70° C. and maintained for 2 hours, filtered, and vacuum dried at 60° C. for 6 hours to obtain the carbon-encapsulated PtCo / C catalyst.

[0064] The ligand compound selected in this embodiment can be replaced by any one of formic acid, thiourea, ammonia monohydrate, and ammonium carbonate; the carbonization compound selected can be replaced by any one of malic acid, dopamine, polydopamine, glucose, and sucrose; the carbonization catalyst selected can be replaced by any one of cobalt chloride, nickel chloride, and nickel nitrate.

[0065] Example 4

[0066] S1. PtCo / C catalyst (Pt content is 28%) is placed in a crucible, and then placed in a 5% hydrogen-argon mixed gas atmosphere at 400°C for 2 hours to obtain a heat-treated PtCo / C catalyst; 50 mg of the heat-treated PtCo / C catalyst is placed in a flask, and then 50 mg of formic acid, 162.6 mg of dopamine, 20 mg of cobalt chloride and 10 ml of isopropanol / water (volume ratio of 50:50) are added and ultrasonicated for 10 minutes, and then the mixture is placed in a 25°C water bath and stirred for 16 hours, the product is collected by centrifugation (10000 rpm, five minutes), and the product is vacuum dried at 60°C for 6 hours to obtain a powder;

[0067] S2. The obtained powder is maintained at 400° C. for 2 hours in a 5% hydrogen-argon mixed gas atmosphere, and finally dispersed in 1M HCl, heated to 70° C. and maintained for 2 hours, filtered, and vacuum dried at 60° C. for 6 hours to obtain the carbon-encapsulated PtCo / C catalyst.

[0068] The ligand compound selected in this embodiment can be replaced by any one of urea, thiourea, ammonia monohydrate, and ammonium carbonate; the carbonization compound selected can be replaced by any one of malic acid, polydopamine, oleylamine, glucose, and sucrose; the carbonization catalyst selected can be replaced by any one of cobalt nitrate, nickel chloride, and nickel nitrate.

[0069] Example 5

[0070] S1. Disperse 25 mg of Vulcan XC-72 in 100 mL of ethylene glycol and then ultrasonicate for half an hour. Add 35 mg of Pt(acac) to the above solution. 2 and 7.8mg Co(acac) 2, stirring in the mixture for 12 hours, after the metal ions are completely mixed on the Vulcan XC-72, the reaction temperature is raised to 180°C, refluxed for 10 hours, and after cooling to room temperature, the product is collected by centrifugation (10000r.pm, five minutes), and the product is vacuum dried at 60°C for 6 hours, then the powder is placed in a crucible, placed in a 5% hydrogen-argon mixed gas atmosphere at 400°C for 2 hours, and after cooling to room temperature, placed in a flask, 50mg urea, 200uL oleylamine, 20mg cobalt nitrate are added and ultrasonicated for 10 minutes, and then the mixture is placed in a 25°C water bath and stirred for 16 hours. The product is collected by centrifugation (10000r.pm, five minutes), and the product is vacuum dried at 60°C for 6 hours to obtain a powder;

[0071] S2. The obtained powder is maintained at 400°C for 2 hours in a 5% hydrogen-argon mixed gas atmosphere, and finally heated to 70°C in 1M HCl and maintained for 2 hours, followed by suction filtration and vacuum drying at 60°C for 6 hours to obtain the carbon-encapsulated PtCo / C catalyst.

[0072] The ligand compound selected in this embodiment can be replaced by any one of formic acid, thiourea, ammonia monohydrate, and ammonium carbonate; the carbonization compound selected can be replaced by any one of malic acid, dopamine, polydopamine, glucose, and sucrose; the carbonization catalyst selected can be replaced by any one of cobalt chloride, nickel chloride, and nickel nitrate.

[0073] Comparative Example 1

[0074] 50 mg of PtCo / C catalyst (Pt content of 28%) was placed in a crucible, and then placed in a 5% hydrogen-argon mixed gas atmosphere at 400° C. for 2 hours to obtain a heat-treated PtCo / C catalyst.

[0075] Comparative Example 2

[0076] S1. Put a PtCo / C catalyst (Pt content is 28%) in a crucible, and then place it in a 5% hydrogen-argon mixed gas atmosphere at 700°C for 2 hours to obtain a heat-treated PtCo / C catalyst; take 50 mg of the heat-treated PtCo / C catalyst in a flask, then add 50 mg of urea, 200 uL of oleylamine, 20 mg of cobalt nitrate and 10 ml of isopropanol / water (volume ratio 50:50) and ultrasonicate for 10 minutes, then place the mixture in a 25°C water bath and stir for 16 hours, collect the product by centrifugation (10000 r.pm, five minutes), and vacuum dry the product at 60°C for 6 hours to obtain a powder;

[0077] S2. The obtained powder is maintained at 400° C. for 2 hours in a 5% hydrogen-argon mixed gas atmosphere, and finally dispersed in 1M HCl, heated to 70° C. and maintained for 2 hours, filtered, and vacuum dried at 60° C. for 6 hours to obtain the carbon-encapsulated PtCo / C catalyst.

[0078] Comparative Example 3

[0079] Take 25 mg of Vulcan XC-72 and disperse it in 100 mL of ethylene glycol, then ultrasonicate for half an hour. Add 35 mg of Pt(acac) to the above solution. 2 and 7.8mg Co(acac) 2 , stirring the mixture for 12 hours, after the metal ions are completely mixed on the Vulcan XC-72, the reaction temperature is raised to 180°C and refluxed for 10 hours. Then it is filtered and dried in an oven at 60°C for 12 hours. Then it is placed in a crucible and maintained at 400°C for 2 hours in a 5% hydrogen-argon mixed gas atmosphere to obtain a heat-treated PtCo / C catalyst.

[0080] Comparative Example 4

[0081] S1. Disperse 25 mg of Vulcan XC-72 in 100 mL of ethylene glycol and then ultrasonicate for half an hour. Add 35 mg of Pt(acac) to the above solution. 2 and 7.8mg Co(acac) 2 , continue stirring in the mixture for 12 hours, after the metal ions are completely mixed on the Vulcan XC-72, raise the reaction temperature to 180°C, reflux for 10 hours, and after cooling to room temperature, collect the product by centrifugation (10000r.pm, five minutes), and vacuum dry the product at 60°C for 6 hours, place the powder in a flask, add 50mg urea, 200uL oleylamine, 20mg cobalt nitrate and ultrasonicate for 10 minutes, then place the mixture in a 25°C water bath and stir for 16 hours. Collect the product by centrifugation again (10000r.pm, five minutes), and vacuum dry the product at 60°C for 6 hours to obtain a powder;

[0082] S2. The obtained powder is maintained at 400°C for 2 hours in a 5% hydrogen-argon mixed gas atmosphere, and finally heated to 70°C in 1M HCl and maintained for 2 hours, followed by suction filtration and vacuum drying at 60°C for 6 hours to obtain the carbon-encapsulated PtCo / C catalyst.

[0083] Compared with Example 5, the difference of this comparative example is that an alloy catalyst without heat treatment is used.

[0084] Comparative Example 5

[0085] S1. Disperse 25 mg of Vulcan XC-72 in 100 mL of ethylene glycol and then ultrasonicate for half an hour. Add 35 mg of Pt(acac) to the above solution. 2 and 7.8mg Co(acac) 2 , continue stirring in the mixture for 12 hours, and after the metal ions are completely mixed on the Vulcan XC-72, raise the reaction temperature to 180°C and reflux for 10 hours. Then filter it with suction, and then dry it in an oven at 60°C for 12 hours. Then place it in a crucible and maintain it at 400°C for 2 hours in a 5% hydrogen-argon mixed gas atmosphere to obtain a heat-treated PtCo / C catalyst;

[0086] S2. The heat-treated PtCo / C catalyst is maintained at 400°C for 2 hours in a 5% hydrogen-argon mixed gas atmosphere, and finally dispersed in 1M HCl, heated to 70°C and maintained for 2 hours, filtered, and vacuum dried at 60°C for 6 hours to obtain the carbon-encapsulated PtCo / C catalyst.

[0087] Compared with Example 5, the difference of this comparative example is that PtCo / C is synthesized by its own method, but urea, oleylamine and cobalt nitrate are not used for treatment.

[0088] Comparative Example 6

[0089] S1. Take 50 mg of PtCo / C catalyst without heat treatment in a flask, then add 50 mg of urea, 200 uL of oleylamine, 20 mg of cobalt nitrate and 10 ml of isopropanol / water (volume ratio 50:50) and ultrasonicate for 10 minutes, then place the mixture in a 25°C water bath and stir for 16 hours, collect the product by centrifugation (10000 rpm, five minutes), and vacuum dry the product at 60°C for 6 hours to obtain a powder;

[0090] S2. The obtained powder is maintained at 400° C. for 2 hours in a 5% hydrogen-argon mixed gas atmosphere, and finally dispersed in 1M HCl, heated to 70° C. and maintained for 2 hours, filtered, and vacuum dried at 60° C. for 6 hours to obtain the carbon-encapsulated PtCo / C catalyst.

[0091] Compared with Example 1, the difference of this comparative example is that a PtCo / C catalyst without heat treatment is used.

[0092] Comparative Example 7

[0093] S1, taking 50 mg of PtCo / C catalyst into a crucible, and then placing it in a 5% hydrogen-argon mixed gas atmosphere at 400° C. for 2 hours to obtain a heat-treated PtCo / C catalyst;

[0094] S2. The heat-treated PtCo / C catalyst is maintained at 400°C for 2 hours in a 5% hydrogen-argon mixed gas atmosphere, and finally dispersed in 1M HCl, heated to 70°C and maintained for 2 hours, filtered, and vacuum dried at 60°C for 6 hours to obtain the carbon-encapsulated PtCo / C catalyst.

[0095] Compared with Example 1, the difference of this comparative example is that urea, oleylamine and cobalt nitrate are not used for treatment.

[0096] Comparative Example 8

[0097] S1. Take 50 mg of commercial PtCo / C catalyst (Pt content is 28%) in a crucible, and then place it in a nitrogen atmosphere at 400°C for 2 hours to obtain a heat-treated PtCo / C catalyst. Take 50 mg of the heat-treated PtCo / C catalyst in a flask, then add 50 mg of urea, 200 uL of oleylamine, 20 mg of cobalt nitrate and 10 ml of isopropanol / water (volume ratio 50:50) and ultrasonicate for 10 minutes, then place the mixture in a 25°C water bath and stir for 16 hours, collect the product by centrifugation (10000 r.pm, five minutes), and vacuum dry the product at 60°C for 6 hours to obtain a powder;

[0098] S2. The obtained powder is maintained at 400° C. for 2 hours in a 5% hydrogen-argon mixed gas atmosphere, and finally dispersed in 1M HCl, heated to 70° C. and maintained for 2 hours, filtered, and vacuum dried at 60° C. for 6 hours to obtain the carbon-encapsulated PtCo / C catalyst.

[0099] Comparative Example 9

[0100] S1. Take 50 mg of commercial PtCo / C catalyst (Pt content is 28%) in a crucible, and then place it in a 5% hydrogen-argon mixed gas atmosphere at 400°C for 2 hours to obtain a heat-treated PtCo / C catalyst. Take 50 mg of the heat-treated PtCo / C catalyst in a flask, then add 50 mg of urea, 200 uL of oleylamine, 20 mg of cobalt nitrate and 10 ml of isopropanol / water (volume ratio 50:50) and ultrasonicate for 10 minutes, then place the mixture in a 25°C water bath and stir for 16 hours, collect the product by centrifugation (10000 r.pm, five minutes), and vacuum dry the product at 60°C for 6 hours to obtain a powder;

[0101] S2. Maintain the obtained powder at 400° C. for 2 hours in a nitrogen atmosphere, and finally disperse it in 1M HCl, heat it to 70° C. and maintain it for 2 hours, filter it, and vacuum dry it at 60° C. for 6 hours to obtain the carbon-encapsulated PtCo / C catalyst.

[0102] Comparative Example 10

[0103] S1. PtCo / C catalyst (Pt content is 28%) is placed in a crucible, and then placed in a 5% hydrogen-argon mixed gas atmosphere at 400°C for 2 hours to obtain a heat-treated PtCo / C catalyst; 50 mg of the heat-treated PtCo / C catalyst is placed in a flask, and then 50 mg of urea, 200 uL of oleylamine and 10 ml of isopropanol / water (volume ratio 50:50) are added and ultrasonicated for 10 minutes, and then the mixture is placed in a 25°C water bath and stirred for 16 hours, the product is collected by centrifugation (10000 r.pm, five minutes), and the product is vacuum dried at 60°C for 6 hours to obtain a powder;

[0104] S2. The obtained powder is maintained at 400° C. for 2 hours in a 5% hydrogen-argon mixed gas atmosphere, and finally dispersed in 1M HCl, heated to 70° C. and maintained for 2 hours, filtered, and vacuum dried at 60° C. for 6 hours to obtain the carbon-encapsulated PtCo / C catalyst.

[0105] Compared with Example 1, the difference of this comparative example is that no cobalt nitrate component is added.

[0106] Comparative Example 11

[0107] S1. Take 50 mg of commercial PtCo / C catalyst (Pt content is 28%) in a crucible, and then place it in a 20% hydrogen atmosphere at 400°C for 2 hours to obtain a heat-treated PtCo / C catalyst. Take 50 mg of the heat-treated PtCo / C catalyst in a flask, then add 50 mg of urea, 200 uL of oleylamine, 20 mg of cobalt nitrate and 10 ml of isopropanol / water (volume ratio 50:50) and ultrasonicate for 10 minutes, then place the mixture in a 25°C water bath and stir for 16 hours, collect the product by centrifugation (10000 r.pm, five minutes), and vacuum dry the product at 60°C for 6 hours to obtain a powder;

[0108] S2. The obtained powder is maintained at 400° C. for 2 hours in a 20% hydrogen atmosphere, and finally dispersed in 1M HCl, heated to 70° C. and maintained for 2 hours, filtered, and vacuum dried at 60° C. for 6 hours to obtain the carbon-encapsulated PtCo / C catalyst.

[0109] Comparative Example 12

[0110] S1. Take 50 mg of commercial PtCo / C catalyst (Pt content is 28%) in a crucible, and then place it in a 20% hydrogen atmosphere at 400°C for 2 hours to obtain a heat-treated PtCo / C catalyst. Take 50 mg of the heat-treated PtCo / C catalyst in a flask, then add 50 mg of urea, 200 uL of oleylamine, 20 mg of cobalt nitrate and 10 ml of isopropanol / water (volume ratio 50:50) and ultrasonicate for 10 minutes, then place the mixture in a 25°C water bath and stir for 16 hours, collect the product by centrifugation (10000 r.pm, five minutes), and vacuum dry the product at 60°C for 6 hours to obtain a powder;

[0111] S2. The obtained powder is maintained at 400° C. for 2 hours in a 5% hydrogen-argon mixed gas atmosphere, and finally dispersed in 1M HCl, heated to 70° C. and maintained for 2 hours, filtered, and vacuum dried at 60° C. for 6 hours to obtain the carbon-encapsulated PtCo / C catalyst.

[0112] Performance Testing

[0113] 1. The carbon-wrapped alloy catalysts prepared in Example 1 and Comparative Examples 1-2 were observed using a transmission electron microscope. Figure 1-4 shown.

[0114] See also Figure 1-4 .Depend on Figure 2 It can be seen that the PtCo alloy particles prepared in Example 1 are wrapped by a thin carbon layer. Figure 3 This shows that the morphology and structure of the heat-treated PtCo / C catalyst in Comparative Example 1 changed little, while the heat treatment temperature in Comparative Example 2 was too high, resulting in an overall increase in the size of the PtCo / C catalyst, and a significant change in the morphology and structure, resulting in a significant decrease in its ECSA and MA. Therefore, the heat treatment temperature of the PtCo / C catalyst should not be too high.

[0115] 2. The carbon-coated alloy catalysts prepared in the examples and comparative examples were subjected to accelerated durability tests. The test method is as follows: The catalysts prepared in the examples and comparative examples were respectively configured into inks, and then spun on disk electrodes (RDE, GC) for ORR performance characterization. Specifically: 1.9 mg of catalyst, 1.9 ml of deionized water, 10 ul of Nafion (perfluorosulfonic acid resin) / ethanol solution (5 wt%) and 0.6 ml of isopropanol were added to a sample bottle and mixed, and ultrasonically dispersed for 30 minutes. Use a pipette to take 16.5 μL of ink and drop it on the GC electrode, and hang it to dry at room temperature at 600 rpm. The catalyst was then subjected to an ORR test in a three-electrode system, in which the Pt mesh was used as the counter electrode, the reversible hydrogen electrode was used as the reference electrode, and the disk electrode was used as the working electrode. Add 0.1 M HClO 4 Nitrogen gas (N) with a purity of 99.999% was introduced into the solution.2 ) for 30 minutes to remove oxygen from the solution. Cyclic voltammetry (CV) scanning was performed at 0.05-1.2V vs. RHE to activate the catalyst at a scanning rate of 50mV / s until the hydrogen adsorption / desorption area peak no longer increased. CV scanning was performed at 0.05-1.2V vs. RHE for 5 cycles at a scanning rate of 20mV / s, and the electrochemical activity area (ECSA) was calculated by selecting a stable CV curve. Then, 0.1M HClO 4 Oxygen (O) is introduced into the solution 2 ) 30min to make the solution reach O 2 Saturation, linear voltammetry (LSV) scan range 0.05 ~ 1.05V vs. RHE, scan rate 10mV s -1 , the rotating disk speed is 1600 rpm. Nitrogen is introduced into the back system and the same operation is performed. The polarization curve obtained is used for background subtraction. The mass specific activity (MA) at 0.9 V is calculated to evaluate the catalytic ability of the catalyst for oxygen reduction reaction.

[0116] 3. The carbon-wrapped alloy catalysts prepared in the examples and comparative examples were subjected to an accelerated durability test. The test method is as follows: The accelerated durability test was carried out at 0 2 Saturated 0.1M HClO 4 The cyclic potential scan was applied at 1600 rpm in the solution at a scan rate of 100 mV / s at 0.6 to 1.1 V vs. RHE for 10,000, 20,000, and 30,000 cycles. After each test, the electrochemical activity area of ​​the catalyst was tested (CV test was performed in a new electrolyte saturated with nitrogen, and the catalyst must be activated again: that is, 50 cycles of CV were performed at a scan rate of 50 mV in an electrolyte saturated with nitrogen, and then the activity was measured) and activity (LSV in an electrolyte saturated with oxygen).

[0117] 4. The catalyst prepared in the embodiment was subjected to Pt content determination. Specifically, 5-10 mg of the sample was placed in a vacuum oven and dried at 80°C for 12 hours. The sample was placed in a test crucible of a thermogravimetric analyzer, and after weighing, air or a mixture of air and an inert gas in a certain proportion was used as the working gas. The gas flow rate was controlled to be 20 mL / min, and the sample was heated from room temperature to an end temperature of 800°C at a heating rate of 2°C / min, and finally cooled to room temperature. The test results are shown in Table 1.

[0118] Table 1 Thermogravimetric analysis results of each sample

[0119]

[0120] Table 2 X-ray spectrometer results of each sample

[0121]

[0122] Table 3 ECSA and MA results of each sample after accelerated durability test

[0123]

[0124] From the experimental data in Table 1, it can be seen that the Pt+Co content of the examples of the present invention and the commercial PtCo / C does not change much, indicating that the modification of the catalyst by the present invention does not have much impact on the alloy itself. Among them, the Pt+Co content of the homemade synthesized catalyst modified in Example 5 is close to that of the homemade synthesized catalyst, both of which are about 60%.

[0125] Depend on Figure 5-8 From Table 3, it can be seen that the ECSA of the catalysts modified by Examples 1 to 5 decreased by less than 15% and the MA loss was less than 20%. This result shows that the carbon layer formed by the carbonized compound, the ligand compound and the carbonized catalyst will block the active sites of some catalysts, resulting in a decrease in its ECSA and MA, but their stability is significantly improved. Specifically, Fig.13 and Fig.14 As shown in Table 3, the MA loss rate of the PtCo / C catalyst modified by Example 1 after 30K cycles of ADT is 13.32%, which is 34.10% lower than that of the unmodified PtCo / C catalyst. In particular, the ECSA loss rate after 30K cycles of ADT is only 2.63%, which shows that the carbon layer formed after modification can effectively protect the PtCo alloy particles and delay their dissolution when the catalyst is working. However, the ECSA and MA of the catalysts modified by Comparative Examples 11-12 are seriously reduced, indicating that the excessive gas reduction during the heat treatment process will destroy the alloy structure.

[0126] Depend on Figure 5 , 6 It can be seen from Tables 2 and 3 that compared with the modified PtCo / C catalyst of Example 1, although the ECSA and MA of the catalyst of Comparative Example 1 remain almost unchanged compared with commercial PtCo / C after heat treatment at 400°C with a 5% hydrogen-argon mixture, the effect on improving stability is minimal. The stability of the catalyst after heat treatment with a 5% hydrogen-argon mixture is slightly improved compared with that before modification. At the same time, the oxygen content decreases and the carbon content increases in the X-ray energy spectrometer results, indicating that heat treatment under reducing gas can effectively improve the defects and oxygen content of the catalyst carrier, increase the degree of graphitization of the carrier, and alleviate carbon corrosion. From the X-ray energy spectrometer (EDS) results of Comparative Example 2, it can be found that the oxygen content has decreased significantly and the carbon content has increased significantly, but its ECSA and MA have both decreased significantly, and the CV curve of the catalyst after heat treatment has changed significantly, and the characteristic peaks of hydrogen adsorption and desorption of Pt appear. At the same time, combined with Figure 4The TEM results show that using too high a heat treatment temperature will destroy the alloy structure, resulting in a significant decrease in its oxygen reduction performance.

[0127] Depend on Figure 9-10 It can be seen from the experimental data in Table 3 that, through the results of Comparative Example 6, it can be seen that if the catalyst is not heat-treated, the carrier may show obvious carbon corrosion during the stability test, resulting in a significant decrease in catalyst performance. Comparative Example 7 does not use urea, oleylamine, and cobalt nitrate for treatment, and a carbon layer cannot be formed, resulting in a significant decrease in the ECSA and MA of the catalyst after stability. Therefore, the carbon layer formed by the modification of Examples 1 to 5 plays a vital role in improving the stability of the PtCo alloy. The stability of the catalyst treated with Comparative Examples 8-9 is improved less, and the activity decreases more. The main reason is that the medium and high temperature nitrogen annealing is not enough to completely carbonize the carbonized compound into a stable carbon layer, which makes this carbon layer easily damaged during the stability test and loses its protective effect on the Pt alloy. The results of Comparative Example 10 show that if a carbonization catalyst is not added during the modification process, the carbon layer formed is unstable, and most of it will dissolve and fall off during the stability test, resulting in the catalyst stability of Comparative Example 10 being worse than that of Examples 1 to 5.

[0128] From Table 3 and Figure 11-12 It can be known that the alloy catalyst with high graphitization and high loading wrapped by the carbon layer prepared in Example 5 effectively improves its stability while maintaining good activity. Specifically, the ECSA after 30,000 cycles of accelerated durability test decreased by 5.21%, while MA decreased by 14.18%. The alloy catalyst prepared in Comparative Example 4 decreased by 8.30% after stability test, while MA decreased by 20.62%. This result further illustrates that the defects and oxygen content of the catalyst carrier can be effectively improved by heat treatment under reducing gas, and then the alloy catalyst is wrapped with a carbon layer, which can improve the stability of the catalyst to oxygen reduction reaction more than the Pt alloy catalyst wrapped with a carbon layer. The alloy catalyst prepared in Comparative Example 3 is only heat treated once, and the alloy catalyst in Comparative Example 5 does not use ligand compounds, carbonized compounds and carbonized catalysts for modification. The ECSA loss rate and MA loss rate of the catalyst finally prepared after 30K cycles of ADT are significantly higher than those in Example 5.

[0129] In summary, this patent effectively improves the defects and oxygen content of the catalyst carrier through a medium heat treatment temperature, and then wraps the alloy catalyst with a carbon layer at a medium annealing temperature, thereby improving its stability while maintaining the performance of the alloy.

[0130] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for preparing a carbon-coated alloy catalyst, characterized in that: The following steps are involved: S1. heat-treating the catalyst in a reducing gas atmosphere, mixing the heat-treated catalyst with a carbonized compound, a ligand compound, a carbonized catalyst, and a solvent, dispersing by ultrasonication, stirring, centrifuging, and drying to obtain a powder; the heat treatment temperature is 200-400°C; S2, annealing the obtained powder in a reducing gas atmosphere, dispersing the annealed powder in an acid solution, heating, filtering, and vacuum drying to obtain the carbon-encapsulated alloy catalyst; The catalyst is a platinum alloy catalyst or an alloy catalyst made from a carrier and a metal precursor; the platinum alloy catalyst includes at least one of PtCo / C, PtCoNi / C and PtNi / C; the carrier includes at least one of carbon black, carbon nanotubes, mesoporous carbon, graphene, carbon nanowires and graphite fibers; The reducing gas in steps S1 and S2 includes at least one of a 5% hydrogen-argon mixed gas, a 5% carbon monoxide-helium mixed gas, and a 5% ammonia-nitrogen mixed gas.

2. The method for preparing the carbon-coated alloy catalyst according to claim 1, characterized in that: At least one of the following (1) to (2): (1) The platinum content of the platinum alloy catalyst is ≥ 20%; (2) The metal precursor includes at least one of chloroplatinic acid, platinum chloride, platinum acetylacetonate, cobalt acetylacetonate, cobalt chloride, nickel acetylacetonate, iron nitrate, and copper acetylacetonate.

3. The method for preparing the carbon-wrapped alloy catalyst according to claim 1, characterized in that: At least one of the following (1) to (4): (1) The carbonized compound includes at least one of malic acid, dopamine, polydopamine, oleylamine, glucose, and sucrose; (2) The ligand compound includes at least one of formic acid, thiourea, ammonia monohydrate, ammonium carbonate, and urea; (3) The carbonization catalyst includes at least one of cobalt chloride, cobalt nitrate, nickel chloride and nickel nitrate; (4) The solvent is alcohol or an alcohol-water solution.

4. The method for preparing the carbon-wrapped alloy catalyst according to claim 1, characterized in that: The mass ratio of the heat-treated platinum alloy catalyst to the carbide compound, the ligand compound, and the carbide catalyst is 1: (1-10): (0.2-2): (0.1-1).

5. The method for preparing a carbon-coated alloy catalyst according to claim 1, characterized in that: The mass ratio of the metal precursor to the carrier, the carbonization compound, the ligand compound, and the carbonization catalyst is 1: (0.5-1): (0.8-8): (0.17-17): (0.09-0.9).

6. The method for preparing the carbon-wrapped alloy catalyst according to claim 1, characterized in that: At least one of the following (1) to (3): (1) The heat treatment time is 1-2 hours; (2) The ultrasonic dispersion time is 10-30 minutes; (3) The stirring time is 12-24 hours.

7. The method for preparing the carbon-wrapped alloy catalyst according to claim 1, characterized in that: At least one of the following (1) to (4): (1) The annealing treatment is performed at a temperature of 400-500°C and for a time of 2-4 hours; (2) The concentration of the acid solution is 1M-1.5M; (3) The heating is to raise the temperature to 70-80°C for 2-12 hours; (4) The vacuum drying is maintained at 60°C for 4-6 hours.

8. A carbon-wrapped alloy catalyst prepared by the method for preparing a carbon-wrapped alloy catalyst as claimed in any one of claims 1 to 7.

9. Use of the carbon-wrapped alloy catalyst as claimed in claim 8 in the preparation of a fuel cell.

Citation Information

Patent Citations

  • Method for improving oxygen reduction electrocatalytic stability of platinum-carbon catalyst

    CN112615016A

  • Platinum-carbon catalyst, carbon material and preparation method and application thereof

    CN114430049A

  • Co@N,S(two)-Kb high-dispersion core-shell structure catalyst and preparing method and application thereof

    CN110102330A

  • Fuel cell cathode catalyst and preparation method thereof, membrane electrode and fuel cell

    CN111725524A